Analisis Proses City Branding’ Taste Of Padang’ sebagai Brand Destinasi Pariwisata Sumatera Barat - Muhammad Rauf Hidayat; Thamrin Thamrin (Jurnal Kajian Manajemen dan Wirausaha, 2019)
Purpose - The purpose of this study was to determine the process and background of theforming of city branding in West Sumatra, namely 'Taste of Padang'.Methodology - This type of research is descriptive causative. This research was conducted inWest Sumatera Province. The research was done in 2019. Researchers generate facts andfindings through interviews and studies of documents related to the brand 'Taste of Padang'.Finding - The results of the study show that city branding 'Taste of Padang' is a sub-brand of'Wonderful Indonesia' initiated by the Ministry of Tourism of the Republic of Indonesia. As arealization, FGD was held to establish a West Sumatra tourism destination brand by the WestSumatra Tourism Department. To become a sub-brand of 'Wonderful Indonesia' in the FGDprocess the establishment of the brand 'Taste of Padang' only focuses on the logo and tagline.Keywords: City Branding, Tourism Brand Destinations, Taste of Padang, West SumatraTourism Office, FGD